The Effect of Gross Regional Domestic Product and Fiscal Decentralization on Supply Chain Fiscal Capacity Management in Papua Province - Marlissa, A. Elsyan Rienette (International Journal of Supply Chain Management, 2020)
This study aims to analyze the Effect of Gross Regional Domestic Product and Supply Chain Fiscal Decentralization on Supply Chain Supply Chain Fiscal Capacity Management in Papua Province. This study used secondary data analyzed by linear regression analysis with pooled data types within 10 years using Two Stage Least Square (2SLS). The results indicate that Gross Regional Domestic Product, Regional Tax, and Regional Retribution simultaneously have a significant effect on Supply Chain Fiscal Capacity Management with a total effect of 91.36 percent, while the remaining 8.64 percent is influenced by other variables not observed in this study.